Analysis of the Role of Muhammadiyah Zakat Infaq and Sadaqah Institutions in the Efficiency of Productive Zakat Fund Management Using the Data Envelopment Analysis (DEA) Approach - Joana Rosie Shabatiny Degely; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to measure the level of efficiency in the financial performance of the Zakat Management Organization (OPZ), namely the Muhammadiyah Amil Zakat Institution (LAZISMU). The population in this study is LAZISMU Sidoarjo. The analytical tool used is a non-parametric quantitative method, namely Data Envelopment Analysis (DEA) with a production approach using DEAP 2.1 software. The type of data used is secondary data in the form of the financial statements of the Indonesian Zakat House for the 2020-2021 period. This study uses 2 assumptions, namely Constant Return To Scale (CRS) and Variable Return to Scale (VRS). Based on the results of research conducted using the Data Envelopment Analysis (DEA) method, the results showed that the performance of Rumah Zakat Indonesia experienced efficiency in 2020 and 2021, which was 100%.